Nanoscale bismuth-based glass fiber composite photocatalytic material and preparation method thereof
By combining Bi2WO6 with chopped glass fibers, a nano-scale bismuth-based glass fiber composite material is solved, and the existing photocatalytic materials have low efficiency in sunlight utilization, insufficient reactive sites and insufficient stability in the sun, achieving high efficiency, Stable photocatalytic effect.
Patent Information
- Application Number
- CN202411567110.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing photocatalytic materials have low utilization efficiency in sunlight, insufficient reactive sites, and insufficient stability and durability, which limits their application in environmental restoration.
Using nano-scale bismuth-based glass fiber composite material, Bi2WO6 is combined with chopped glass fibers as a catalyst, modifiers are used to improve the dispersion and exposure of the material, and enhance the absorption and utilization of sunlight.
It improves the catalytic efficiency and stability of photocatalytic materials, enhances the absorption and utilization of ultraviolet rays and visible light, extends the service life of the material, and expands its application adaptability in complex environments.
Smart Images

Figure HDA0005119533510000011 
Figure HDA0005119533510000012 
Figure HDA0005119533510000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalysis, and in particular to a nano-level bismuth-based glass fiber composite photocatalytic material and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of industrialization and urbanization, environmental problems have increased year by year. Human consumption and livestock farms have caused a large amount of organic matter in surface water to exceed the standard. The organic matter that cannot be completely metabolized remains in the water environment, causing serious biological toxicity. Pollutants such as dyes, antibiotics, and pesticides remaining in water bodies can damage liver and kidney functions, reduce immune function, and endanger human health. Traditional water treatment processes have been used to remove many common pollutants in water, but organic pollutants are highly toxic, such as organic dyes and antibiotics that exist in water bodies at a microscopic scale and cannot be completely removed by the above processes. In order to reduce the environmental burden and avoid harm to human health, it is urgent to develop a more effective and sustainable method to eliminate organic pollution.
[0003] Photocatalytic technology is a pollutant treatment process that uses visible light and ultraviolet light combined with low-dose photocatalysts to mineralize toxic and harmful organic pollutants into non-toxic and harmless small molecules. Many photocatalytic materials such as ZnO, SnO2 and TiO2 have been widely studied for environmental remediation due to their good photochemical stability, high photocatalytic activity and low cost. However, due to the wide band gap, photocatalytic reactions can only be carried out under ultraviolet (UV) excitation, resulting in low solar energy conversion efficiency. Sunlight contains only 5% ultraviolet light, as well as 43%-46% visible light and 49%-52% near-infrared (NIR) light. Therefore, it is necessary to develop photocatalytic materials that can respond to visible light and effectively utilize near-infrared light for environmental photocatalysis. Compared with other treatment processes, photocatalytic technology uses renewable light energy and has the advantages of low energy consumption and low cost.
[0004] In recent years, double-helix photocatalysts, especially bismuth-based nanocomposites, have become a hot topic in the research and industrial communities due to their excellent photocatalytic performance and unique physicochemical properties. As a new type of photocatalyst, bismuth-based nanocomposites show significant advantages over traditional materials. These materials not only exhibit excellent electrical, optical, magnetic, photocatalytic and thermal properties, but also show outstanding application potential in sensing and environmental governance. Their suitable band structure enables bismuth-based materials to efficiently absorb visible light, so they are widely regarded as ideal choices for photocatalytic applications. Bismuth-based photocatalysts such as Bi2O3, Bi2S3, BiFeO3, Bi2MoO6, Bi2WO6 and BiOX (X=Cl, Br, I) have shown excellent activity in the degradation of organic pollutants and environmental remediation due to their narrow band gap structure and excellent light absorption ability. However, despite its multiple advantages in performance, it still faces some challenges, such as the stability of photocatalytic efficiency and performance degradation after long-term use. In addition, the complexity and cost issues in the preparation process limit its widespread use in industrial applications.
[0005] Existing photocatalytic materials have the following disadvantages:
[0006] 1. Defects in light energy absorption and utilization: Photocatalytic materials usually have a high absorption capacity for specific parts of the spectrum (such as ultraviolet light). However, the proportion of ultraviolet light in sunlight is low, and in practical applications, the absorption and conversion efficiency of light by photocatalytic materials is often limited. This leads to low light energy utilization in actual operation, and the efficiency of photocatalytic reactions may not be high even if exposed to light sources for a long time. In addition, photocatalytic materials may also be interfered by other light sources, such as visible light or infrared light, further reducing their light energy utilization.
[0007] 2. Insufficient reactive sites: The number of reactive sites of photocatalytic materials has an important influence on the reaction efficiency. However, the reactive sites of existing photocatalytic materials may be few or unevenly distributed, which limits the rate and effect of the photocatalytic reaction. In actual operation, even if the amount of photocatalytic material is increased, the reaction efficiency may not be significantly improved because the number of reactive sites has not been substantially increased.
[0008] 3. Insufficient stability and durability: During long-term illumination or catalytic reaction, the structure and performance of photocatalytic materials may change, resulting in reduced stability and durability. For example, some photocatalytic materials may undergo photocorrosion or changes in lattice structure under illumination, thereby reducing their catalytic activity. In addition, the loss and poisoning of the catalyst may also affect the stability and durability of the material. In addition, most photocatalytic materials are currently nanopowder materials, which have application defects such as difficulty in recycling and difficulty in repeated use on the basis of insufficient durability. Summary of the invention
[0009] The main purpose of the present invention is to provide a nano-scale bismuth-based glass fiber composite photocatalytic material with improved catalytic efficiency and stability and a preparation method thereof.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing a nano-scale bismuth-based glass fiber composite photocatalytic material comprises the following steps:
[0012] (1) Pretreatment: adding a modifier to the chopped glass fibers to react with the modifier to obtain modified glass fibers;
[0013] The modifier is silane coupling agent KH-550, aminosilane coupling agent, epoxysilane coupling agent or methacrylate coupling agent;
[0014] (2) Synthesis: 9.5 g Bi(NO3)3·5H2O and 3.95 g Na2WO4·5H2O were dissolved in 100-500 mL deionized water to obtain a mixed solution. The modified glass fiber was impregnated with the mixed solution and then transferred to a reactor for thermochemical reaction. After the reaction was completed, the obtained white precipitate was centrifuged and washed to obtain a Bi2WO6-based chopped glass fiber composite photocatalytic material.
[0015] The chopped glass fibers are subjected to extraction and cleaning treatment before adding the modifier. After adding the modifier to the chopped glass fibers, the chopped glass fibers are stirred at 70-90° C. and at a stirring speed of 200-400 rpm / min for 4-6 hours, and then the chopped glass fibers are filtered out and placed in a vacuum drying oven, dried for 2-4 hours at a vacuum degree of 0.07-0.09 MPa and 85-105° C., and heated for modification at 90-150° C. for 10 minutes to 1 hour.
[0016] The mass ratio of Bi(NO3)3·5H2O to Na2WO4·5H2O is 9.5:3.95;
[0017] The concentration of the mixed solution is 0.02-0.1 mol / L.
[0018] Furthermore, 5 g to 15 g of the modified glass fiber is soaked in every 100 mL of the mixed solution.
[0019] The modified glass fiber is impregnated for 1-5 hours.
[0020] Further, Bi(NO3)3·5H2O and Na2WO4·5H2O were dissolved in deionized water and stirred at a stirring speed of 200-400 rpm / min for 1-2 h.
[0021] The reaction temperature in the reactor is 100-200° C., and the reaction time is 3-15 hours.
[0022] The white precipitate is centrifuged 3-5 times, the speed of the centrifugation is 2000-3500 rpm / min, and the time of the centrifugation is 3-5 min;
[0023] The washing is performed by washing with distilled water and ethanol 3 to 5 times respectively.
[0024] Furthermore, the washed product is dried in a hot air furnace at 50-70° C. for 6-12 hours to obtain a Bi2WO6-based chopped glass fiber composite photocatalytic material.
[0025] The present invention also provides a nano-level bismuth-based glass fiber composite photocatalytic material, which is prepared according to the preparation method.
[0026] By means of the above technical solution, the present invention has at least the following advantages:
[0027] 1. Optimizing material dispersibility and active site exposure: In view of the non-negligible shortcoming of easy recombination of photogenerated electrons and holes in the photocatalytic process of bismuth-based semiconductors, the present invention produces nanoparticles in the generation of bismuth tungstate, and adopts a method of preparing the catalyst into nano-scale particles and combining them with a strong fiber carrier. This can reduce the band gap energy of the catalyst material, absorb sunlight in a larger wavelength range, and shorten the migration distance of photogenerated carriers from the catalyst body to the surface, which can effectively inhibit the recombination of photogenerated electrons and holes.
[0028] 2. Improve catalytic efficiency and stability: The nano-scale bismuth-based oxygen-containing acid salts in the Bi2WO6-based short-cut glass fiber composite photocatalytic material of the present invention have a wider solar light absorption range and high photocatalytic activity, which can effectively improve the absorption and utilization capabilities of ultraviolet and visible light; the short-cut glass fiber carrier has good biocompatibility, stability and non-toxicity, etc., which can further improve the reflection and absorption of ultraviolet and visible light, while increasing the mechanical strength, so that subsequent application forms can be expanded.
[0029] 3. Enhanced application adaptability in complex media: Short-cut glass fibers introduce hydrophobic organic groups through surface modification, which can change the surface properties of photocatalytic materials and improve their compatibility and dispersibility in organic systems. This improvement enables bismuth-based photocatalysts to better adapt to complex environmental conditions, such as organic wastewater treatment and air purification, thereby expanding their practical application areas and effectiveness.
[0030] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a photocatalytic degradation curve diagram of each embodiment provided by the embodiments of the present invention;
[0032] Figure 2 is a scanning electron microscope image of Example 1 provided in an embodiment of the present invention;
[0033] Figure 3 This is a scanning electron microscope image of Example 6 provided in the embodiments of the present invention. DETAILED DESCRIPTION
[0034] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0035] Embodiment 1:
[0036] (1) Pretreatment: Add γ-methacryloxypropyltrimethoxysilane, i.e., silane coupling agent KH570, to the chopped glass fibers after extraction and cleaning, stir at 80°C and 300 rpm / min for 5 h, filter out the chopped glass fibers, put the chopped glass fibers into a vacuum drying oven, and dry them for 3 h at a vacuum degree of 0.08 MPa and 95°C. After the water is evaporated, heat at 120°C for 30 min to allow the chopped glass fibers to fully react with the modifier, and obtain the modified glass fibers;
[0037] (2) Synthesis: Bi2WO6-based short glass fiber composites were prepared by hydrothermal method. 9.5g Bi(NO3)3·5H2O and 3.95g Na2WO4,5H2O were dissolved in 250mL deionized water and stirred continuously at a stirring speed of 300rpm / min for 1.5h to form a white mixed solution with a concentration of 0.04mol / L. Thereafter, 100mL of the mixed solution was infiltrated into 10g of modified glass fiber for 3h. The infiltrated mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene and kept at 180℃ for 12h to obtain a white precipitate. The white precipitate was centrifuged 5 times, each time at a speed of 3000rpm / min for 3min, and washed with distilled water and ethanol 5 times each. Finally, the obtained product was dried in a hot air furnace at 60℃ for 10h to obtain Bi2WO6-based short glass fiber composite photocatalytic material.
[0038] Embodiment 2:
[0039] (1) Pretreatment: adding epoxy silane coupling agent to the chopped glass fibers after extraction and cleaning, stirring at 70°C and 200 rpm / min for 6 h, filtering out the chopped glass fibers, placing the chopped glass fibers in a vacuum drying oven, drying them at 85°C for 4 h under the conditions of vacuum degree of 0.07 MPa, and drying for 4 h, heating at 90°C for 1 h after the water is evaporated, allowing the chopped glass fibers to fully react with the modifier, and discharging the modified glass fibers;
[0040] (2) Synthesis: Bi2WO6-based short glass fiber composites were prepared by hydrothermal method. 9.5g Bi(NO3)3·5H2O and 3.95g Na2WO4, 5H2O were dissolved in 100mL deionized water and stirred continuously at a stirring speed of 200rpm / min for 2h to form a white mixed solution with a concentration of 0.1mol / L. Thereafter, 100mL of the mixed solution was infiltrated into 10g of modified glass fiber for 5h. The infiltrated mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and kept at 100℃ for 15h to obtain a white precipitate. The white precipitate was centrifuged 4 times, each time at a speed of 2000rpm / min for 5min, and washed with distilled water and ethanol 3 times each. Finally, the obtained product was dried in a hot air furnace at 70℃ for 6h to obtain Bi2WO6-based short glass fiber composite photocatalytic material.
[0041] Embodiment 3:
[0042] (1) Pretreatment: Add methacrylate coupling agent to the chopped glass fibers after extraction and cleaning, stir at 90°C and 400 rpm / min for 4 h, filter out the chopped glass fibers, put the chopped glass fibers into a vacuum drying oven, and dry them for 2 h at a vacuum degree of 0.09 MPa and 105°C. After the water is evaporated, heat at 150°C for 10 min to allow the chopped glass fibers to fully react with the modifier, and obtain the modified glass fibers;
[0043] (2) Synthesis: Bi2WO6-based short glass fiber composites were prepared by hydrothermal method. 9.5g Bi(NO3)3·5H2O and 3.95g Na2WO4,5H2O were dissolved in 500mL deionized water and stirred at 400rpm / min for 1h to form a white mixed solution with a concentration of 0.02mol / L. Thereafter, 100mL of the mixed solution was infiltrated into 5g of modified glass fiber for 1h. The infiltrated mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene and kept at 200℃ for 3h to obtain a white precipitate. The white precipitate was centrifuged 3 times, each time at a centrifugal speed of 3500rpm / min for 4min, and washed with distilled water and ethanol 4 times respectively. Finally, the obtained product was dried in a hot air furnace at 50℃ for 12h to obtain Bi2WO6-based short glass fiber composite photocatalytic material.
[0044] Embodiment 4:
[0045] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0046] The impregnated mixture was reacted in the autoclave for 6 h.
[0047] Embodiment 5:
[0048] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0049] The impregnated mixture was reacted in an autoclave at a temperature of 150°C.
[0050] Embodiment 6:
[0051] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0052] The time for the chopped glass fiber to fully react with the modifier is 1h;
[0053] 9.5 g Bi(NO3)3·5H2O and 3.95 g Na2WO4, 5H2O were dissolved in 500 mL deionized water.
[0054] Embodiment 7:
[0055] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0056] 9.5 g Bi(NO3)3·5H2O and 3.95 g Na2WO4, 5H2O were dissolved in 500 mL deionized water.
[0057] Embodiment 8:
[0058] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0059] The modifier is silane coupling agent KH-550.
[0060] The photocatalytic performance of the Bi2WO6-based chopped glass fiber composite photocatalytic material prepared in each embodiment was comprehensively evaluated according to the following detection method:
[0061] In order to evaluate the degradation efficiency of the photocatalytic material, the following experiment was conducted: First, 8 portions of 50 mL of a methylene blue solution with a concentration of 100 mg / L were prepared and mixed with 50 mg of the photocatalytic materials of Examples 1 to 8, respectively. Then, the above mixture was dispersed for 30 minutes using ultrasonic dispersion technology to ensure that the photocatalytic material was evenly distributed in the solution.
[0062] Next, the dispersed solution is placed in a photoreactor, the light source is turned off, and a dark adsorption process of 30 min is carried out to reach adsorption-desorption equilibrium. After the dark adsorption is completed, the light source is turned on, and samples are taken at the time points of 2 min, 5 min, 10 min, 20 min, 30 min and 40 min. After each sampling, a quencher is used to terminate the reaction immediately to ensure that the reaction will not continue during the sampling process. Subsequently, the solution after sampling is transferred to a liquid chromatograph for a pollutant concentration test to measure the residual concentration of methylene blue at each time point. The concentration data obtained by the liquid chromatograph is used to calculate the degradation rate at different time points, and a photocatalytic degradation curve is drawn to compare the photocatalytic efficiency of each embodiment.
[0063] The experimental results are as follows Figure 1 As shown, Figure 1 The horizontal axis Time is the time in minutes, and the vertical axis C / C0 is the ratio of the reactant concentrations. Figure 1It can be seen that the optimal composite photocatalytic material prepared by the present invention has an excellent photocatalytic effect. The composite material used in Example 1 achieved a photocatalytic degradation rate of more than 95% in the experiment, showing excellent performance. Compared with Example 8, Example 1 adopted different surface modifiers, among which γ-methacryloxypropyltrimethoxysilane has a better effect on the surface activity stimulation of glass fibers. Examples 2 and 3 were compared with Example 1 in terms of multiple factors. The most prominent factors were the difference in the type of glass fiber modifier and modification time, and the Bi2WO6 loading amount (related to the growth concentration). The Bi2WO6 loading amount was related to the concentration of the mixed solution and the amount of glass fiber infiltrated with a certain amount of the mixed solution after modification. The data showed that Example 1 had the best photocatalytic effect, among which the appropriate type of modifier and modification time had the most important influence on the process of nanoparticle in-situ loading of glass fibers, followed by the difference in the influence of the loading amount, which also accounted for a large proportion, but under different conditions, the interaction of various factors could obtain better catalytic performance.
[0064] In order to further explore the factors affecting the photocatalytic effect, comparative tests were conducted on reaction temperature, reaction time, modification time and reactant concentration in Examples 4 to 8. The results show that the changes in reaction time and reaction temperature have a significant impact on the progress of the photocatalytic reaction, slowing down the reaction rate and causing the final degradation rate to drop by about 10-50%. Among them, Examples 4 and 5 reduced the reaction concentration during the preparation of the reactants, such as Figure 2 As shown, this is a scanning electron microscope (SEM) image of Example 1. Figure 3 As shown, it is the SEM image of Example 6. The precursor concentrations of Example 1 and Example 6 are different. Comparing the two SEM images, the results show that the loading rate of the nanocatalytic material on the surface of the final glass fiber is correspondingly reduced, which in turn affects its photocatalytic performance, which is worse than that of Example 1.
[0065] It can be seen that the loading amount of nanocatalytic materials on the glass fiber surface has an important influence on the final photocatalytic performance. Appropriate selection of surface modifiers and optimization of reaction conditions are crucial for the preparation of efficient composite photocatalytic materials.
[0066] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a nano-scale bismuth-based glass fiber composite photocatalytic material, characterized in that: The following steps are involved: (1) Pretreatment: adding a modifier to the chopped glass fibers to react with the modifier to obtain modified glass fibers; The modifier is silane coupling agent KH-550, aminosilane coupling agent, epoxysilane coupling agent or methacrylate coupling agent; (2) Synthesis: Bi(NO3)3·5H2O and Na2WO4·5H2O were dissolved in deionized water to obtain a mixed solution, the modified glass fiber was impregnated with the mixed solution, and then transferred to a reactor for a thermochemical reaction. After the reaction was completed, the obtained white precipitate was centrifuged and washed to obtain a Bi2WO6-based chopped glass fiber composite photocatalytic material.
2. The preparation method according to claim 1, characterized in that: The chopped glass fibers are subjected to extraction and cleaning treatment before adding the modifier. After adding the modifier to the chopped glass fibers, the chopped glass fibers are stirred at 70-90° C. and at a stirring speed of 200-400 rpm / min for 4-6 hours, and then the chopped glass fibers are filtered out and placed in a vacuum drying oven, dried for 2-4 hours at a vacuum degree of 0.07-0.09 MPa and 85-105° C., and heated for modification at 90-150° C. for 10 minutes to 1 hour.
3. The preparation method according to claim 1, characterized in that: The mass ratio of Bi(NO3)3·5H2O to Na2WO4·5H2O is 9.5:3.95; The concentration of the mixed solution is 0.02-0.1 mol / L.
4. The preparation method according to claim 3, characterized in that: Every 100 mL of the mixed solution is soaked with 5 g to 10 g of the modified glass fiber.
5. The preparation method according to claim 4, characterized in that: The modified glass fiber is impregnated for 1-5 hours.
6. The preparation method according to claim 5, characterized in that: Dissolve Bi(NO3)3·5H2O and Na2WO4·5H2O in deionized water and stir at a stirring speed of 200-400 rpm / min for 1-2 h.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The reaction temperature in the reactor is 100-200° C., and the reaction time is 3-15 hours.
8. The preparation method according to claim 7, characterized in that: The white precipitate is centrifuged 3-5 times, the speed of the centrifugation is 2000-3500 rpm / min, and the time of the centrifugation is 3-5 min; The washing is performed by washing with distilled water and ethanol 3 to 5 times respectively.
9. The preparation method according to claim 8, characterized in that: The washed product is dried in a hot air oven at 50-70° C. for 6-12 hours to obtain a Bi2WO6-based chopped glass fiber composite photocatalytic material.
10. A nano-scale bismuth-based glass fiber composite photocatalytic material, characterized in that: It is prepared according to the preparation method described in any one of items 1-9.
Citation Information
Patent Citations
Preparation method and application of graphene-blended Bi2WO6 microcrystalline glass fiber mesh
CN108927144A
Preparation method and application of glass fiber cloth loaded W / BiVO4 photocatalyst
CN111744549A